PEMETAAN BATIMETRI PANTAI MALALAYANG DUA, KOTA MANADO - Abdulrahman Lahay; Rignolda Rignolda Djamaluddin; Hermanto W K Manengkey; Brama Djabar (Sam Ratulangi University, 2020)
As with other coastal areas, Malalayang Dua Coast has been used for various activities and is predicted to continue to grow along with the development of Manado City. To support efforts to manage and utilize coastal space in an effective and sustainable manner, data and information are needed related to oceanographic factors, one of which is the bathymetry condition of the coastal waters. This research was carried out with the aim of describing the bathymetric conditions and analyzing the slope of the bottom of the waters. The depth measurement by acoustic method was carried out along 15 survey lines and 750 fixed measurement points, and the bathymetry map was drawn with reference to Mean Seawater Level (MSL). The results obtained indicate that the bathymetry of Malalayang Dua Coast in the west has shallow waters that are wider than the eastern one. Meanwhile, parts of the waters deeper up to a depth of 50 m appear to be steeper in the West than on the East side. In the middle part of the observed waters, there is a part that is relatively deep and protrudes towards the land with a steeper side towards the east. The slope of the bottom of the water in the west (Profile 1) is indicated by flat slopes (2.6%) to a depth of 7 m, and slopes (13%) at a depth of 7 m to 50 m. In the middle section (Profile 2) the slope is categorized as gentle (3%) to a depth of 4 m, and inclined slopes (10%) at a depth of 4 m to 50 m. In the eastern part (Profile 3) the slopes are categorized as sloping slopes (10.28) to a depth of 35 m, and gentle slopes (3.42%) at a depth of 35 m to 50 m. Keywords: bathymetry, acoustics, slope, Malalayang Dua CoastAbstrakSebagaimana wilayah pantai pada umumnya, Pantai Malalayang Dua telah dimanfaatkan untuk berbagai aktivitas dan diprediksi akan terus berkembang seiring perkembangan Kota Manado. Untuk menunjang upaya pengelolaan dan pemanfaatan ruang pantai secara efektif dan berkelanjutan, diperlukan data dan informasi terkait faktor oseanografi dimana salah satu yang penting yaitu kondisi batimetri perairan pantai tersebut. Penelitian ini dilaksanakan dengan tujuan untuk menggambarkan kondisi batimetri dan menganalisis kemiringan lereng dasar perairan. Pengukuran kedalaman dengan metode akustik dilakukan sepanjang 15 lajur perum dan 750 titik fix perum, dan peta batimetri digambarkan dengan referensi Muka Laut Rata-rata (Mean Seawater Level - MSL). Hasil yang diperoleh menunjukkan bahwa batimetri Pantai Malalayang Dua sebelah Barat memiliki perairan dangkal yang lebih lebar dibandingkan sebelah Timur. Sementara itu, untuk bagian perairan yang lebih dalam hingga kedalaman 50 m nampak lebih terjal di bagian Barat dibandingkan sisi sebelah Timur. Pada bagian tengah perairan yang diamati, terdapat bagian yang relatif dalam dan menjorok ke arah darat dengan sisi yang lebih terjal ke arah sebelah Timur. Kemiringan lereng dasar perairan di sebelah Barat (Profil 1) terindikasi lereng datar (2,6%) hingga kedalaman 7 m, dan lereng miring (13%) pada kedalaman 7 m hingga 50 m. Pada bagian tengah (Profil 2) kemiringan lereng terkategori landai (3%) hingga kedalaman 4 m, dan lereng miring (10%) pada kedalaman 4 m hingga 50 m. Pada bagian Timur (Profil 3) kemiringan lereng terkategori lereng miring (10,28) hingga kedalaman 35 m, dan lereng landai (3,42%) pada kedalaman 35 m hingga 50 m. Kata kunci: batimetri, akustik, kemiringan lereng, Pantai Malalayang Dua